2015
DOI: 10.1016/j.seares.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Is long-term ecological functioning stable: The case of the marine benthos?

Abstract: It is widely acknowledged that human activities are contributing to substantial biodiversity loss and that this threatens ecological processes underpinning human exploitation of 'ecosystem services' (defined by the Millennium Ecosystem Assessment as 'the benefits people obtain from ecosystems'). In the present study we consider three 'intermediate ecosystem services' in both contemporary and ancient marine systems and although 'ecosystem services' per se did not exist in the Jurassic our study seeks to conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 48 publications
(71 reference statements)
4
9
0
Order By: Relevance
“…On the other hand, SI fluxes were similar to those at DDL and SoGC. A previous study reported no consistent changes in ecosystem function with changes in functional diversity (Frid and Caswell, 2015) and we also found consistent differences in benthic communities at our study sites but not in benthic flux rates. Therefore, the specific attributes of our study system provide an opportunity to evaluate the contribution of environmental variables and functional diversity to benthic flux variation.…”
Section: Benthic Fluxes and Benthic Community Spatial Variationsupporting
confidence: 72%
“…On the other hand, SI fluxes were similar to those at DDL and SoGC. A previous study reported no consistent changes in ecosystem function with changes in functional diversity (Frid and Caswell, 2015) and we also found consistent differences in benthic communities at our study sites but not in benthic flux rates. Therefore, the specific attributes of our study system provide an opportunity to evaluate the contribution of environmental variables and functional diversity to benthic flux variation.…”
Section: Benthic Fluxes and Benthic Community Spatial Variationsupporting
confidence: 72%
“…To our knowledge, this is the first study comparing long‐term trends and multi‐decadal dynamics in multiple dimensions of functional community change across trophic groups and areas. Previous trait‐based studies on long‐term functional community change have focused on single organism groups separately, either zoobenthos (Gogina, Darr, & Zettler, ; Neumann & Kröncke, ; Veríssimo et al, ; Weigel, Blenckner, & Bonsdorff, ) or fish (Baptista, Martinho, Nyjtrai, Pardal, & Dolbeth, ; Barcelo, Ciannelli, Olsen, Johannessen, & Knutsen, ; Dencker et al, ; Frelat et al, ), and particularly multi‐trait compositional changes on local scale (Clare, Robinson, & Frid, ; Frid & Caswell, ).…”
Section: Discussionmentioning
confidence: 99%
“…References Aller (1983), Bremner (2008), Bremner et al (2006), Costello et al (2015), Frid and Caswell (2016) predator An organism that feeds by preying on other organisms (e.g., starfish) FH6 parasite/commensal An organism that lives in or on another living organism (the host), from which it obtains food and other requirements Function Can indicate hydrodynamic conditions (suspension feeders in turbulent, deposit feeders in calmer water), carbon transport between pelagos and benthos (suspension feeders) and backwards (predators) and vulnerability (e.g., surface deposit feeders and suspension feeders are more sensitive to trawling). Impacts resource utilization and facilitation (e.g., deposit feeders facilitate microbes that further decompose organic carbon).…”
Section: Remarkmentioning
confidence: 99%
“…Bolam et al (2014),Bremner et al (2008),Frid and Caswell (2016),Törnroos and Bonsdorff (2012) used -alongside substratum affinity -for habitat classification. Can depict depth distribution of other traits.…”
mentioning
confidence: 99%